2014
DOI: 10.1002/jrs.4592
|View full text |Cite
|
Sign up to set email alerts
|

Micro Raman investigation on corrosion of Pb‐based alloy replicas of letters from the museum Plantin‐Moretus, Antwerp

Abstract: To better understand corrosion behaviour of lead (Pb)-based alloys exposed to volatile organic compounds – specifically acetic\ud and formic acid – a preliminary research has been carried out on laboratory-made samples replicating such alloys. Replicas have\ud been manufactured by simulating specific types of Pb-based alloys, with antimony (Sb) and tin (Sn) as alloying elements, in order to\ud characterise corrosion products and evaluate the influence of each alloying element. Replicas were cast in a refractor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Recent research has shown that the presence of antimony strongly promotes the corrosion of lead. 33 This was also recorded in the analysis of the heavily corroded type objects from the Plantin-Moretus Museum collection. There, it became clear that type with high levels of antimony and no (or very low amounts) of tin were prone to a severe corrosion process.…”
Section: Corrosion Due To Acidic Environmentsmentioning
confidence: 91%
“…Recent research has shown that the presence of antimony strongly promotes the corrosion of lead. 33 This was also recorded in the analysis of the heavily corroded type objects from the Plantin-Moretus Museum collection. There, it became clear that type with high levels of antimony and no (or very low amounts) of tin were prone to a severe corrosion process.…”
Section: Corrosion Due To Acidic Environmentsmentioning
confidence: 91%
“…At lower acid concentrations lead formate hydroxide (ICDD 14-0831) was detected in these lab experiments, instead of neutral lead formate but this compound has yet not been reported on heritage objects. The influence of the alloying elements tin and antimony on corrosion by organic acids has been studied on letter replicas [66].…”
Section: Lead Formatementioning
confidence: 99%
“…Ghiara and co‐workers carried out a micro‐Raman investigation on corrosion of Pb‐based alloy replicas of letters from the museum Plantin‐Moretus, Antwerp. In this work's perspective, the influence of Sb as an alloying element on the corrosion of Pb‐based artifacts may generate serious problems when such objects have to be restored, and particular attention should be given to conservation/stabilization procedures . Gutman et al .…”
Section: Art and Archeologymentioning
confidence: 99%